Does Inorganic Nitrogen Fertilization Improve Soil Aggregation? Insights from Two Long‐Term Tillage Experiments. Issue 3 (1st May 2014) - Blanco‐Canqui, Humberto; Ferguson, Richard B.; Shapiro, Charles A.; Drijber, Rhae A.; Walters, Dan T.
Abstract : The relationship between inorganic fertilization and soil aggregation is not well understood. We studied cumulative nitrogen (N) fertilization impacts on aggregation, soil organic C (SOC), pH, and their relationships under irrigated and rainfed experiments in Nebraska after 27 and 28 yr, respectively. The dominant soil series were Crete silt loam at the irrigated site, and Coleridge silty clay loam at the rainfed site. We studied irrigated continuous corn ( Zea mays L.) in chisel plow (CP) and ridge till (RidgeT) receiving 0, 75, 150, and 300 kg N ha −1 yr −1 and rainfed continuous corn and corn–soybean [ Glycine max (L.) Merr.] in moldboard plow (MP), reduced till (RT), and no‐till (NT) with corn receiving 0, 80, and 160 kg N ha −1 yr −1 . Fertilization altered soil aggregation in all tillage systems under continuous corn. Mean weight diameter of water‐stable aggregates (MWDA) increased in the upper 7.5‐cm depth in NT but decreased in the 7.5‐ to 60‐cm depth by 1.5 times with N application. Fertilization reduced pH but had little or no effect on SOC. Both MWDA and pH ( r = 0.47***) decreased under irrigated corn, particularly in the 7.5‐ to 30‐cm depth. No‐till and RT had two to five times greater near‐surface MWDA than MP. Continuous corn had greater MWDA than corn–soybean in the upper 30‐cm depth except in MP. Long‐term N fertilization improves near‐surface soil aggregation in NT continuous corn but reduces aggregation in the subsoil. Results also suggest that, if fertilizers are applied at rates of about 80 kg N ha −1, deterioration of soil aggregation would be minimal.